Mutagenic and tumourigenic properties of the spores of Aspergillus clavatus. - Blyth, W. (Nature Publishing Group, 1982)
Spore walls of a sputum-derived isolate of Aspergillus clavatus yielded mutagen(s) when their extracts were fractionally precipitated with ethanol following alkaline hydrolysis. After spores were given by nasal inoculation to 6-8-week-old CF-1 mice, light and electron microscopy of lung sections showed that they had been readily phagocytozed by the polymorphonuclear leucocytes and alveolar macrophages mobilized during early allergic alveolitis in immunized mice. The formation of phagosomes was followed in thioglycollate-stimulated peritoneal macrophages grown in vitro. Unimmunised mice showed a comparable lung reaction, attributed to pulmonary mycotoxicosis, and revealed a rising incidence of lung tumours, from 25% at 2 months from inoculation, to 27.3% at 6 and to 55.5% at 8. Mean numbers of tumours per lung rose from 1.0 to 2.2. Total tumours, including lymphomas, reached a final incidence of 77.7% at 8 months, when control animals were tumour-free. Tumour development correlated with the retention of apparently intact spores within giant cells probably derived from aggregates of alveolar macrophages. The implications of these findings in the light of the known history of human exposure to such spores is discussed. IMAGES: